Prospek Praktik Mikro Inkubator “Entrepreneur Passion” dalam Membina Wirausahawan Pelajar (Milenialpreneur) - Vembri Aulia Rahmi (Universitas Islam Kadiri, 2020)
In general, business incubators are created to provide space and facilities, especially for new entrepreneurs pioneering or running a business. Its existence was first initiated by universities so that it is expected to be able to build a sustainable and beneficial business ecosystem for end-users as business stakeholders. During this time the practice of incubators business is carried out in the form of programs or projects for a certain period from the beginning of the registration selection until participants reach the level of business creation, namely by students. While this research was conducted to explore how the implementation of business incubator programs that occur in high schools, even though the type of business incubator is a micro-level business incubator or can be called a business incubator simulation practice. The study was conducted at one of the Private High Schools in Indonesia. By using a qualitative descriptive analysis approach through data collection and interviews with teachers and students, especially for those who are involved in extra activities outside school hours